Africanidades: a lei n. 10.639/03 na visão de professores - Arruda, Marcelo Guimarães (2013)
10.639/03, in two public high schools of São Paulo, located in the north of the capital, which are part of the same jurisdictional Board of Education. The investigation sought to ascertain how the inclusion of the issue of African History and Culture in the school curriculum is being done, how teachers are being trained on this topic and what is their perception of the Law. Data collection was conducted through a questionnaire sent to two pedagogical coordinators at the Board of Education and through semi structured interviews with three teachers of a school and a teacher from the second school. The results show that there is a work done by the Board of Education, directed to the implementation of the law through the implementation of some federal projects, providing continuing education for pedagogical coordinators, teachers and representatives of this area, which should act as multipliers at the school level. But schools still walk at a very slow pace, performing occasional activities without an interdisciplinary integration. The data analysis also reveals a certain discomfort of some teachers while discussing this theme, and not everyone agrees with the need for such a Law. The study suggests that much remains to be done in education in order to build new racial ethnic relations